Vernacularization and bilingualism among the Sundanese; A case study of Kawi culture - Gunawan, Aditia (Wacana, Journal of the Humanities of Indonesia, 2025)
This article examines the linguistic landscape of pre-modern Sunda, drawing on documents from the fourteenth to sixteenth centuries. The study highlights the significant role of Old Javanese as a cosmopolitan-vernacular language among Sundanese intellectuals, shaping bilingual practices in the region. Employing the framework of language order, which posits that languages are hierarchically structured within a culture, this research seeks to address the question: what roles did Old Sundanese and Old Javanese play within the language order of Sundanese society? To answer this, the study first traces the circulation of Old Javanese texts in the Sundanese region, analysing their impact on local literary and religious traditions. It then explores explicit and implicit references to the Old Javanese language in Old Sundanese sources to assess its perceived status. Finally, the article investigates sociolinguistic interactions in fifteenth-century Sunda by analysing code-switching and translation strategies, revealing the depth of linguistic interaction between Old Sundanese and Old Javanese. The findings indicate that Old Javanese functioned as a key medium for intellectual and religious discourse in West Java from the eleventh to the sixteenth century. The vernacularization of Old Javanese texts into Old Sundanese works, such as Sasana Mahaguru, demonstrates conscious linguistic adaptation to local audiences. Contrary to prevailing assumptions, Sundanese bilingualism was not merely a consequence of Mataram’s political dominance but was deeply rooted in premodern linguistic and intellectual exchanges, where Kawi culture played a central role in transmitting supralocal knowledge to Sundanese scholars.